Organizational Citizenship Behavior as a Mediator of Transformational Leadership and Employee Performance in Engineering Firms - Irna Dalimunthe; Rahmat Agus Santoso; F. Risallah (Global Research Collaboration, 2026)
Employee performance has become a critical issue in the engineering sector due to increasing organizational complexity, technological advancement, and the demand for effective teamwork and operational efficiency. In this context, transformational leadership is considered an important leadership approach that can enhance employee performance by encouraging positive organizational behavior such as Organizational Citizenship Behavior (OCB). However, previous studies have shown inconsistent findings regarding the direct and indirect relationship between transformational leadership, OCB, and employee performance, particularly in the engineering sector. This study aims to examine the mediating role of Organizational Citizenship Behavior in the relationship between transformational leadership and employee performance in the engineering sector. The study employed a quantitative research approach with an explanatory research design. Data were collected through structured questionnaires distributed to employees working in engineering-related organizations. The sampling technique used purposive sampling with a total of 200 respondents. The collected data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS-SEM) approach through SmartPLS software. The findings revealed that transformational leadership has a positive and significant effect on employee performance and Organizational Citizenship Behavior. In addition, Organizational Citizenship Behavior was found to significantly influence employee performance. The study also confirmed that Organizational Citizenship Behavior significantly mediates the relationship between transformational leadership and employee performance. These results indicate that transformational leaders are able to improve employee performance not only directly but also indirectly by fostering voluntary organizational behavior among employees. This study contributes to the development of organizational behavior and leadership literature by providing empirical evidence regarding the mediating role of Organizational Citizenship Behavior in the engineering sector.